Musculoskeletal Symptoms and Assessment of Ergonomic Risk Factors on a Coffee Farm - Carla Estrada-Muñoz; Héctor Madrid-Casaca; Guido Salazar-Sepúlveda; Nicolás Contreras-Barraza; José Iturra-González; Alejandro Vega-Muñoz (Applied Sciences, 2022)
In Honduras, some coffee farms must comply with strict standards of social, economic, and environmental sustainability, due to their organic, gender and fair-trade certifications. The principal research aim is to evaluate the musculoskeletal risks in occupations in a Honduran coffee farm certified in sustainable environments and to know the status of its workers within the farm. Musculoskeletal symptom perception during the last twelve months was consulted, assessing exposure to risk factors for work-related musculoskeletal disorders using the Quick Exposure Check method. Data regarding 48 workers were analyzed to provide the results. Within the body regions where discomfort is concentrated, the back, shoulders, wrists, knees, and feet stand out, and the highest risk exposures are presented for the coffee cutters at the neck level and in the wrist/hand segment, in the coffee pickers at the back, shoulder–arm segment, and wrist/hand segment, and in the processors in the back area and shoulder–arm segment. It is concluded that, in all the coffee fruit harvesting processes, the people who work in these jobs are exposed to ergonomic risks.